Modelling, Analysis and Optimization of a 4th Order Delta-Sigma ADC and its Non-Idealities for Audio Codec Applications Achieving Dynamic Range Above 100dB - Singh, Bramh Dev; Naskar, Sourav; Das, Subhajit; Rahaman, Hafizur (2021 International Symposium on Devices, Circuits and Systems (ISDCS), 2021)
In this work, The presented MATLAB ® SIMULINK ® model of the 4 th order single bit Δ∑ Modulator and Decimator Filter for the Audio Codec applications. The Delta-Sigma ADC is developed along with the various Non-idealities and noise models associated with the Δ∑ Modulator. This type of modulators is designed for Audio Codec applications that require high accuracy at the frequency of input needed. Here the targeted SNR is minimum of 100 dB at an output data rate of 48KS/s. The presented Simulink ® model is a 4 th order 1-bit CIFF Modulator structure. The various Non-Idealities like the practical GBW, switch noise, clock jitter, finite DC gain can affect the performance of ideal Δ∑ Modulators; hence in this work, the non-idealities have been added for all stages and optimized them for achieving the 10dB Dynamic Range with practical conditions.